Role of hippocampal circKcnk9 in visceral hypersensitivity and anxiety comorbidity of irritable bowel syndrome - Liu, Yuan; Chen, Zhong; Lin, Wei; Zhou, Yifei; Liu, Zihan; Zhao, Ruixia; Chen, Yu; Wu, Bin; Chen, Aiqin; Lin, Chun (Frontiers in Cellular Neuroscience, 2022)
Abstract Irritable bowel syndrome (IBS) is a common gastrointestinal disorder characterized by recurrent visceral pain and altered bowel habits (diarrhea or constipation). However, the molecular and pathological mechanisms are poorly understood. In this study, neonatal colorectal distension was found to induce visceral hypersensitivity and anxiety. The expression of hippocampal circKcnk9, a novel circRNA, was significantly increased in IBS-like rats. Interestingly, CA1 shcircKcnk9 treatment inhibited long-term potentiation (LTP) and alleviated visceral hypersensitivity and anxiety in IBS-like rats, whereas overexpression of CA1 circKcnk9 induced LTP, visceral hypersensitivity, and anxiety in controls. Several experiments indicated that increased CA1 circKcnk9 acted as an miR-124-3p sponge, which resulted in the inhibitory effect of miR-124-3p on gene silencing. There was a negative correlation between circKcnk9 and miR-124-3p expression. As expected, CA1 administration of agomiR-124-3p decreased CA1 LTP, visceral hypersensitivity, and anxiety in the IBS-like rats. In contrast, CA1 treatment with antagomiR-124-3p induced LTP, visceral hypersensitivity, and anxiety in the controls. Furthermore, bioinformatic analysis and experimental data showed that EZH2 is a circKcnk9/miR-124-3p target gene, and increased EZH2 expression was involved in visceral hypersensitivity and anxiety in IBS-like rats by enhancing hippocampal synaptic plasticity. In conclusion, early life stress induces increased expression of circKcnk9 in the CA1 of IBS-like rats. Increased circKcnk9 expression regulates synaptic transmission and enhances LTP, leading to visceral hypersensitivity and anxiety in IBS-like rats. The underlying circKcnk9 signaling pathway is miR124-3p/EZH2. Increased circKcnk9 reinforces its sponging of miR124-3p and strongly suppresses miR124-3p activity, resulting in increased expression of the target gene EZH2. This study provides a new epigenetic mechanism for visceral hypersensitivity and anxiety in IBS-like rats.